2020
DOI: 10.3390/cells9122712
|View full text |Cite
|
Sign up to set email alerts
|

Entacapone Treatment Modulates Hippocampal Proteins Related to Synaptic Vehicle Trafficking

Abstract: Entacapone, a reversible inhibitor of catechol-O-methyl transferase, is used for patients in Parkinson’s disease because it increases the bioavailability and effectiveness of levodopa. In the present study, we observed that entacapone increases novel object recognition and neuroblasts in the hippocampus. In the present study, two-dimensional electrophoresis (2-DE) and matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry were performed to compare the abundance profiles of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 79 publications
(89 reference statements)
0
2
0
Order By: Relevance
“…185 In addition, entacapone enhances hippocampal synaptic plasticity by increasing the expression of hippocampal proteins dynamin I and synapsin I which control synaptic plasticity via BDNF-TrkB. 186 Besides, tolcapone improves the activity of dopaminergic neurons in the cerebral cortex thereby augments cerebral neurological conductivity. 187 Giakoumaki et al 188 revealed that tolcapone enhances working memory and psychomotor performance in animal model through modulation the BDNF expression.…”
Section: Comt Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…185 In addition, entacapone enhances hippocampal synaptic plasticity by increasing the expression of hippocampal proteins dynamin I and synapsin I which control synaptic plasticity via BDNF-TrkB. 186 Besides, tolcapone improves the activity of dopaminergic neurons in the cerebral cortex thereby augments cerebral neurological conductivity. 187 Giakoumaki et al 188 revealed that tolcapone enhances working memory and psychomotor performance in animal model through modulation the BDNF expression.…”
Section: Comt Inhibitorsmentioning
confidence: 99%
“…Findings from a preclinical study observed that entacapone improves hippocampal neurogenesis through activation of the BDNF–TrkB‐pCREB pathway in mice 185 . In addition, entacapone enhances hippocampal synaptic plasticity by increasing the expression of hippocampal proteins dynamin I and synapsin I which control synaptic plasticity via BDNF–TrkB 186 . Besides, tolcapone improves the activity of dopaminergic neurons in the cerebral cortex thereby augments cerebral neurological conductivity 187 .…”
Section: Activators Of Bdnf/trkb Signalling In Pdmentioning
confidence: 99%